The Life-Cycle Dynamics of Exporters and Multinational Firms - Anna Gumpert; Andreas Moxnes; Natalia Ramondo; Felix Tintelnot (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
This paper studies the life-cycle dynamics of exporters and multinational enterprises (MNEs). We present a dynamic model of trade and MNE activity in which the mode of serving a market depends on the well-known proximity-concentration tradeoff. We show that the option of performing MNE activities in the model produces life-cycle patterns for exporters that differ from those in an export-only model. Calibrating our model to rich firm-level data from France and Norway, our main quantitative finding is that a reduction in trade costs triggers much larger responses in growth rates and exit rates, for young exporters, in the model with MNEs than in the model without MNEs. We also show that the model is largely consistent with a set of new facts on the joint life-cycle dynamic behavior of exporters and MNEs.
Keywords: F01; F02; 330; international trade; exporters; multinational firm; markov process; sunk cost; proximity-concentration tradeoff; trade liberalization